Sources of information about dietary fibre: a cross-sectional survey of 1034 respondents from across Croatia - Sarić, MM (2020)
Nutritional knowledge and attitudes are important for the consumption of healthy food. Well-informed consumers could have a higher chance to select food rich in nutrients like dietary fibre (DF), which is recognized as one of the major determinants for the improvement of health. Due to that reason, health institutions (health centres and hospitals); media (radio, television and internet); education institutions (schools) and education materials (books and magazines) as main sources of information through which people become aware or acquire knowledge of DF, were considered. Cross-sectional survey was conducted from October 2014 to March 2015 on a non-probabilistic sample of 1034 participants from Croatia. The instrument was a questionnaire of self-response, aimed at collecting information on knowledge, attitudes and sources about DF. Descriptive and inferential statistics were performed using SPSS 22.0 software considering a level of significance of 5%. The internet, the preferred source of information, got the highest scores for urban areas, university level of education and for female gender. The radio, the least scored source of information, was preferred by men and with lower education (primary school). People get most information through the internet due to easy access, but it could be detected as a possible risk given the impossibility to control information made public on the internet. It is very important to increase the impact of health centres and schools as adequately controlled public health informing sources.